Biomedical Engineering Systems and Technologies: 11th International Joint Conference, BIOSTEC 2018, Funchal, Madeira, Portugal, January 19–21, 2018, Revised Selected Papers - Cliquet Jr., Alberto; Wiebe, Sheldon; Anderson, Paul; Saggio, Giovanni; Zwiggelaar, Reyer; Gamboa, Hugo; Fred, Ana; Bermúdez i Badia, Sergi (Communications in computer and information science, 2019)
Biomedical Electronics and Devices -- Bioimaging -- Bioinformatics Models, Methods and Algorithms -- Health Informatics